Penerapan Prinsip Ultra Petita dalam Putusan Mahkamah Konstitusi di Indonesia - Michael Dolf Lailossa; Parbuntian Sinaga; Retno Kus Setyowati (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the application of the ultra petita principle in decisions of the Constitutional Court of the Republic of Indonesia, focusing on the case study of Decision Number 90/PUU-XXI/2023. The ultra petita principle is classically understood as a prohibition for judges to rule beyond what is explicitly requested by the parties to the case. However, in practice, the Constitutional Court often uses this principle flexibly to ensure substantive justice and the effective protection of citizens' constitutional rights. This shows how constitutional adjudication in Indonesia tends to prioritize substantive justice over procedural limitations. This thesis aims to analyze the legal basis used by the Constitutional Court when deciding ultra petita cases, while also examining the resulting legal implications for the administrative system of lawmaking in Indonesia. Using a normative legal approach, this study finds that the Constitutional Court positions itself as the sole interpreter of the constitution with progressive authority. In this sense, the Court's decisions may expand its role beyond the traditional boundaries of judicial authority. However, the Constitutional Court's ultra petita practice has the potential to raise concerns about judicial overreach. Ultra petita decisions not only resolve constitutional disputes but also have the potential to create new legal norms that can directly influence the legislative process and even change the structure of national law. Such outcomes raise the question of how to maintain a balance between judicial activism and legislative supremacy. Therefore, it is crucial to establish clear legal boundaries to ensure the Court remains within the constitutional framework, upholds the principle of checks and balances, and prevents conflicts of authority between branches of state power. Therefore, this research contributes to the academic understanding of the dynamics of the Constitutional Court's authority and the urgency of strengthening the rules of the game in maintaining harmony in the Indonesian state system.